Implementasi Flipped Classroom pada Materi Whole Mount (Asetolisis Polen dan Spora) untuk Meningkatkan Pemahaman Mahasiswa - Puspita Ratna Susilawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
The implementation of the flipped classroom model was one of the efforts to prepare quality human resources and master the skills of the 21st century. Face-to-face activities that were more of an analysis, evaluating, and creating in a flipped classroom could train critical thinking skills and had a direct impact on students' understanding. The purpose of this study was to analyze the implementation of the flipped classroom model and its effect on students' understanding of the whole mount material (pollen and spore acetolysis) in microtechnique courses. This research was a quasi-experiment with nonequivalent control group design. The independent variable was the flipped classroom model, while the dependent variable was student understanding. Test (pretest and posttest) was used as data collection techniques. Data analysis was performed by calculating the N-gain then t-test. The learning design was divided into pre-class, in-class, and post-class stages. The in-class stage is designed using the practicum method. The results showed that the percentage of students with high and moderate N-gain categories in the control group was 43.76%, while in the treatment group was higher, namely 64.87%. The implementation of a flipped classroom could improve student understanding of lecture material.